2010
DOI: 10.1002/mats.200900056
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Kinetics in Free‐Radical Polymerization: Prediction of Thermodynamic and Kinetic Parameters Based on ab initio Calculations

Abstract: Initiation kinetics in free radical polymerization is investigated using density functional theory. Thermodynamic and kinetic parameters of the initiation reactions are predicted, and the role of the initiators in the polymerization process is evaluated. Methyl acrylate, methyl methacrylate, acrylonitrile, and styrene homo‐polymerizations with different initiators are studied. Reaction enthalpy and activation energy for each reaction between monomer and the radical fragments arising from the initiators have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
6
26
0
Order By: Relevance
“…Starting from these data, frequencies of molecular species, energetic reaction profiles, vibrational transition state structures, and reaction frequency factors can be obtained explicitly and directly [62][63][64][65][66]. The rate constant of reactions involved in a FRP system can be expressed through the Arrhenius equation.…”
Section: Quantum Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from these data, frequencies of molecular species, energetic reaction profiles, vibrational transition state structures, and reaction frequency factors can be obtained explicitly and directly [62][63][64][65][66]. The rate constant of reactions involved in a FRP system can be expressed through the Arrhenius equation.…”
Section: Quantum Chemistrymentioning
confidence: 99%
“…In particular, propagation reaction of alkenes that are characterized by very simple molecular structures such as ethene [84,85], vinyl chloride [86,87], and acrylonitrile [86][87][88] were studied. Gradually, the interest was turned to the study of homopolymer systems of more complex monomers such as styrene and various acrylates [66,89] and to that of monomers with larger substituent [88,90] such as α-substituted acrylates [91].…”
Section: From Initiation To Propagationmentioning
confidence: 99%
“…Wavefunction‐based quantum chemical methods and DFT have been successfully applied to determine geometries of molecules, transition states, reaction mechanisms, and rate constants of initiation, propagation and chain transfer reactions in high temperature and controlled radical polymerization of acrylates and methacrylates . Various DFT functionals have been successfully applied to study large polymeric systems . It was shown that the 1:5 backbiting mechanism is preferred to 1:3 and 1:7 in thermal polymerization of acrylonitrile .…”
Section: Introductionmentioning
confidence: 99%
“…Various DFT functionals have been successfully applied to study large polymeric systems . It was shown that the 1:5 backbiting mechanism is preferred to 1:3 and 1:7 in thermal polymerization of acrylonitrile . Degirmenci et al studied the propagation of methyl acrylate using B3LYP, MPW1K, BB1K, MPWB1K, and MPW1B95.…”
Section: Introductionmentioning
confidence: 99%
“…Two DFT functionals have been used to calculate the exchange and correlation energies. In addition to the B3LYP,19, 20 which has been extensively used in our previous works,7, 13, 14, 21–25 we adopted the novel hybrid meta DFT method MPWB1K developed by Zhao and Truhlar,26 based on modified Perdew and Wang exchange functional (MPW) and Becke's 1995 correlation functional (B95). As refinement of our previous calculations,14 simulations with the B3LYP functional have been performed using the 6‐311+G(d,p) basis set,27 while the 6‐31G(d,p) basis set has been used with the MPWB1K functional 28…”
Section: Computational Detailsmentioning
confidence: 99%